The dynamics of Pandanus illustrations from a historical perspective - Vera Budi Lestari Sihotang (Research Center for Biology, 2013)
Pandanaceae is placed in the superorder Pandaniflorae and the order Pandanales, indicating its uniqueness when compared with the other seed plants. Pandanaceae contains three genera, Pandanus, Sararanga and Freycinetia. Limited collections seem to be one reason why botanical illustrations are made, so that people can enjoy their